THE INTERNAL AUDIT OF THE QUALITY MANAGEMENT SYSTEM IN THE ROAD TRANSPORT COMPANY - Dobrotkova, Marta; Vrabel, Jan (Doprava a spoje, 2010)
To verify the requirements of the quality management system is very important for each company, which implemented this system into its process. The internal quality audit is the one way how to find out if this system is implemented correctly, the mail task of this audit is to find activities and opportunities for the next improvement.